A közúti forgalom alakulása Mezőhegyesen: 1995-2008 - Zsótér, Brigitta (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
To sum it up, it can be said that winding-up of the sugar factory had an effect on the public traffic, too. I drew a parallel between the traffic and the motor vehicle stock. There was a serious decrease which could be observed in case of both the traffic and the motor vehicle stock. In the road-section of Battonya-Mezőhegyes the average daily traffic and the traffic of heavy goods vehicle significantly decreased in this critical period of time. Consequently, from the point of view of the tetrahedron-model, the following assertion is true: change in economic sphere influenced the infrastructural sphere, too.